Dekonstruksi Seni Lukis Tradisional Jelekong sebagai Ekspresi Visual - Shopia Himatul Alya; Ariesa Pandanwangi; Ismet Zainal Effendi (Ideas Publishing, 2023)
Jelekong has a productive community of artists who produce commercial and mass paintings. This creation aims to create novelty in Jelekong painting by borrowing Jacques Derrida s Deconstruction to present alternative meanings. The creation method used is Alma M. Hawkins creation method which includes the stages of 1) exploration, 2) improvisation, and 3) implementation. The results of the creation of this work are two works entitled